Risk factors for drug nonadherence in antidepressant-treated patients and implications of pharmacist adherence instructions for adherence improvement - Murata, Atsunobu (Dove Medical Press, 2012)
BACKGROUND: The aim of this study was to determine the characteristics of drug adherence in antidepressant-treated versus antidepressant-naïve patients using Drug Attitude Inventory (DAI)-10 scores for nonadherence, to examine the contribution of patient variables such as age, gender, education, prescription contents, side effects, and type of depression (melancholic, nonmelancholic, bipolar) to the reported DAI-10 score, and to examine the efficacy of pharmacist adherence instruction on adherence with antidepressant therapy. METHODS: The subjects were 71 antidepressant-treated inpatients (17 with melancholic depression, 35 with nonmelancholic depression, and 19 with bipolar depression) and 80 antidepressant-naïve inpatients. In the antidepressant-treated patients, self-management of drug intake and pharmacist adherence instruction was initiated after depressive symptoms were in remission, and pharmacist adherence instruction was conducted until the day of discharge. RESULTS: There were no significant differences in baseline characteristics between antidepressant-naïve and antidepressant-treated patients. In antidepressant-treated patients, the mean DAI-10 total score was significantly lower and awareness of side effects was significantly higher than in antidepressant-naïve patients who have never taken antidepressants, nor been referred to psychiatry services (according to pharmacist interviews and medical records). On the first day of self-management of drug intake, the DAI-10 total score in patients with melancholic and bipolar depression was significantly lower than that in patients with nonmelancholic depression. On the day of discharge, there was a significant improvement of DAI-10 total score in all antidepressant-treated patients, and the DAI-10 total score in patients with melancholic depression was significantly lower than that in patients with nonmelancholic depression. The limitation of the study was the small sample size and the fact that we followed only acute phase inpatients. However, the findings seem particularly robust in view of this. CONCLUSION: Risk factors for nonadherence included side effects of antidepressant treatment and type of depression. The results presented here suggest that patients with melancholic depression may be more vulnerable to nonadherence, and that pharmacist adherence instruction may improve nonadherence in antidepressant-treated patients according to type of depression.